2021
DOI: 10.1186/s12964-020-00667-x
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid promotes metastatic niche formation in bone metastasis of colorectal cancer

Abstract: Background To investigate the effect of lactic acid (LA) on the progression of bone metastasis from colorectal cancer (CRC) and its regulatory effects on primary CD115 (+) osteoclast (OC) precursors. Methods The BrdU assay, Annexin-V/PI assay, TRAP staining and immunofluorescence were performed to explore the effect of LA on the proliferation, apoptosis and differentiation of OC precursors in vitro and in vivo. Flow cytometry was performed to sort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…It was reported that high active Warburg effect could be detected in colorectal cancer cells [24]. In our previous study, we found lactate could promote the production of CXCL10 in early OCPs to recruit CD4+ T cells [25]. Together with this study, these results indicated that lactate may broadly modulate the secreting spectrum of chemoattractant proteins to facilitate the formation of metastatic microenvironment.…”
Section: Discussionsupporting
confidence: 78%
“…It was reported that high active Warburg effect could be detected in colorectal cancer cells [24]. In our previous study, we found lactate could promote the production of CXCL10 in early OCPs to recruit CD4+ T cells [25]. Together with this study, these results indicated that lactate may broadly modulate the secreting spectrum of chemoattractant proteins to facilitate the formation of metastatic microenvironment.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies have revealed that lactate contributes to the development of bone metastasis by directly regulating osteoclastogenesis. Qian et al reported that lactic acid promoted a bone metastatic niche for colorectal cancer 38 . Osteoclasts incorporate lactate that is released from breast cancer cells through MCT1 and use this lactate as a fuel to increase oxidative metabolism, thereby promoting bone resorption 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of tumor microenvironment on OCPs or OCs has been deeply investigated in several tumors with high incidence of bone metastasis, such as breast cancer, lung cancer and prostate cancer (Aukes et al 2017 ; Grano et al 2000 ). Although our previous studies demonstrated that CRC cells could regulate osteoclastogenesis after bone metastasis of CRC (Zi-Chen et al 2020 ; Qian et al 2021 ), the process of how osteoclastogenesis is regulated by microenvironment of CRC is still far from clear.…”
Section: Introductionmentioning
confidence: 94%